A Career in IT? The Meanings of a Career at Business Process Outsourcing Centers in Poland from a Biographical Perspective - Pilch, Szymon (Qualitative Sociology Review, 2023)
The paper reconstructs the ways of attributing meanings to IT specialists’ careers at BPO (Business Process Outsourcing) centers in Poland. The findings rely on empirical data, collected through autobiographical narrative interviews. The technique of analysis applied in the study was inspired by grounded theory methodology and allowed for the identification of a basic social process at the analytical stage, namely, “career planning.” On the one hand, the analysis also showed how IT specialists’ careers are given meanings concerning career planning; there seem to be three main ways of understanding one’s career in IT: (1) in terms of reaching economic and social stability, (2) as a transition period in a career as an IT specialist, (3) with regard to becoming an expert in IT. On the other hand, the second axis of analysis has been conceptualized, which is comprised of other subjective and objective elements that may shape career planning. These include the biographical experiences of work, the context of the Polish BPO industry, and career planning resources. Furthermore, a typology consisting of three ways of attributing meanings to IT specialists’ careers at BPO centers has been put forward and analyzed.